2020
DOI: 10.3390/molecules25173928
|View full text |Cite
|
Sign up to set email alerts
|

The Authentication of Java Turmeric (Curcuma xanthorrhiza) Using Thin Layer Chromatography and 1H-NMR Based-Metabolite Fingerprinting Coupled with Multivariate Analysis

Abstract: The identification of adulteration practices of medicinal plants used as herbal medicine is very important to ensure the quality, safety, and efficacy. In this study, thin layer chromatography (TLC) and proton nuclear magnetic resonance (1H-NMR)-based metabolite fingerprinting coupled with multivariate analysis were used for authentication of Curcuma xanthorrhiza extract from Curcuma aeruginosa. Curcumin contents obtained from C. xanthorrhiza extract from various regions were in the range of 0.74%–1.23%. Meanw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Therefore, spectroscopic-based methods in combination with multivariate data analysis (MDA) or chemometrics were potential to be employed since this combination method was provided the way to analyze such an environmental big data [15]. Ultraviolet, visible, and vibrational spectroscopy (infrared and Raman) [16,17], and NMR spectroscopy [18] are widely reported for authentication of Curcuma species. NMR spectroscopy offers some advantages for authentication of medicinal plants such as fast time analysis, simple in sample preparation, high reproducibility, and high robust.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, spectroscopic-based methods in combination with multivariate data analysis (MDA) or chemometrics were potential to be employed since this combination method was provided the way to analyze such an environmental big data [15]. Ultraviolet, visible, and vibrational spectroscopy (infrared and Raman) [16,17], and NMR spectroscopy [18] are widely reported for authentication of Curcuma species. NMR spectroscopy offers some advantages for authentication of medicinal plants such as fast time analysis, simple in sample preparation, high reproducibility, and high robust.…”
Section: Introductionmentioning
confidence: 99%
“…1 H-NMR spectroscopy and chemometrics have also been used for authentication of C. longa adulterated with C. manga and C. heyneana [7,24]. Authentication of C. xanthorrhiza from C. aeruginosa has been successfully investigated using 1 H-NMR and multivariate analysis [18]. However, study on authentication of Curcuma species from different origins using 1 H-NMR spectroscopy is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular techniques for the classification of herbal products include linear discriminant analysis (LDA), k-nearest neighbor, soft independent modeling of class analogy (SIMCA), ANN, partial least square-discriminant analysis (PLS-DA), and orthogonal projections to latent structures-discriminant analysis (OPLS-DA) (Gad and Bouzabata, 2017). Table 1 explains several analytical methods that have been reported which applied the fingerprinting analytical approach using chromatography [Thin-layer chromatography (TLC), GC, and HPLC/ultraperformance liquid chromatography] and spectrometry (UV-Vis, Infrared, near magnetic resonance (NMR), and MS) or both in tandem like gas chromatography-mass spectrometer (GC-MS) and liquid chromatography-mass spectrometer that could be used for fingerprint analysis and authentication of some herbal medicines (Rohman et al, 2020b;Septyanti et al, 2016).…”
Section: Authentication Of Herbal Medicinesmentioning
confidence: 99%
“…By using the developed methods using 1 H-NMR spectroscopy and TLC methods combined chemometrics of PCA, OPLS-DA was successfully used for classifying between pure and adulterated samples such as Curcuma species, especially C. longa adulterated with C. manga (Windarsih et al, 2018), and java turmeric (Rohman et al, 2020b) which can be observed in Figure 2. Other methods for analytical techniques such as polarography, X-ray fluorescence spectrometry, inductively coupled plasmaoptical emission spectroscopy (ICP-OES), and inductively coupled plasma-mass spectrometry (ICP-MS) were combined with multivariate PCA and LDA for the classification and authentication of varieties of Piper betle (Atikul Islam et al, 2020).…”
Section: Authentication Of Herbal Medicinesmentioning
confidence: 99%
“…OPLS-DA is a supervised statistical method of discriminant analysis and a regression modeling method of the multidependent variable to the multi-independent variable [42]. Its greatest feature is that the data variation that is irrelevant with the classification variable Y in the independent variable X can be removed [43] so that the classification information is mainly concentrated in a principal component, and thus the model becomes simple and easy to explain [41]. An OPLS-DA model of different parts of Rana chensinensis was established by using PUFAs data after orthogonal signal correction, which can improve the reliability of the model.…”
Section: Orthogonal Partial Least Squares Discriminant Analysis (Opls-da)mentioning
confidence: 99%